Bovine pericardium in penile prosthesis reimplantation - Eduardo J. Lopes; Tarsila C. Santos; Modesto Jacobino (International Brazilian Journal of Urology, 2007)
We present a case of a patient who underwent a late penile prosthesis implant using bovine pericardium as a complement to the tunica albuginea involved in intense fibrosis that destroyed the corpus cavernosum after an infectious manifestation. The advantages of using bovine pericardium in the substitution of the tunica albuginea are discussed and its first use as a penile prosthesis lining is reported.